A DFT study of the ionic [2+2] cycloaddition reactions of keteniminium cations with terminal acetylenes. Issue 16 (22nd April 2015) - Domingo, Luis R.; Ríos-Gutiérrez, Mar; Pérez, Patricia
Abstract: The molecular mechanism of the ionic [2+2] cycloaddition (I-22CA) reactions of a keteniminium cation (KC) with acetylene and propyne has been investigated using DFT methods at the MPWB1K/6-311G(d, p) level. These I-22CA reactions take place via a two-step mechanism. The first step is the nucleophilic attack of these alkynes on the central carbon of KC, yielding cyclopropene intermediates, while the second step corresponds to the conversion of these intermediates into more stable cyclobuteniminium cations (CCs). The first step is the rate-determining step, while the second step is responsible for the formation of the two regioisomeric CCs experimentally observed in the reaction with propyne. Analysis of the DFT reactivity indices indicates that the strong electrophilic character of KC accounts for the feasibility of these I-22CA reactions. An ELF topological analysis of the changes of the electron density along the IRCs of the two reaction steps allows the molecular mechanism of these I-22CA reactions to be established. Graphical abstract: